What Is Behind the Fluctuations in Seniors’ Poverty Rates in Canada from 1976-2019? - Priyanka Sibal; Dennis Raphael (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2023)
In this article we consider the factors driving variations in poverty rates among Canadian seniors from 1976-2019. Using the international poverty line which is defined as living with less than 50 percent of national median income—measured in Canada through the Low-income measure after tax (LIM-AT)—senior poverty rates declined from 1980 to the mid-1990s but have since increased. Yet according to the Canadian government’s official poverty indicator, the Market Basket Measure (MBM), senior poverty rates remain very low. We investigate these differences in poverty rates over time and consider the implications for seniors’ health and well-being. We find that increasing LIM-AT poverty rates are being driven by growing income inequalities among seniors resulting from differential access to Canada’s pension plan, employer-sponsored and private pension plans as well as growing income inequalities between seniors and the working-age population. The MBM is not sensitive to these growing inequalities. We consider these findings within a political economy lens that places Canada’s undeveloped public pension system within the liberal welfare state’s preference for the private rather than public provision of economic resources. We conclude with recommendations for research and action to ensure Canada’s growing senior population is provided with the conditions and means necessary for health and well-being.